2020
DOI: 10.1111/ejss.12884
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the arbuscular mycorrhizal fungal community and changes in diversity of the rhizosphere of Clematis fruticosa over three seasons across different elevations

Abstract: Clematis fruticosa Turcz. is a dominant native shrub with the potential for spontaneous vegetation succession for restoration of the ecologically fragile and arid Daqing Mountains of Inner Mongolia, which represent an important ecological transition zone in northern China. However, knowledge regarding the interactions between native species and their root-associated arbuscular mycorrhizal (AM) fungi across different seasons and elevation gradients remains obscure. High AM fungal spore density, root colonizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Additionally, the results of this study are similar to those published previously, which revealed that Glomus species were the most abundant among the AMF species studied [33,63]. There has been repeated confirmation that Glomus has a widespread distribution and is able to adapt to a wide variety of ecosystems on a global scale, especially under extreme environmental conditions [64,65]. As Glomus species can typically produce large numbers of spores and fragments of hyphae, they can colonize and spread widely to plants' roots [66].…”
Section: Patterns Of Am Fungal Keystone Taxasupporting
confidence: 90%
“…Additionally, the results of this study are similar to those published previously, which revealed that Glomus species were the most abundant among the AMF species studied [33,63]. There has been repeated confirmation that Glomus has a widespread distribution and is able to adapt to a wide variety of ecosystems on a global scale, especially under extreme environmental conditions [64,65]. As Glomus species can typically produce large numbers of spores and fragments of hyphae, they can colonize and spread widely to plants' roots [66].…”
Section: Patterns Of Am Fungal Keystone Taxasupporting
confidence: 90%
“…Zhao et al (2019) showed that plant community succession has an important influence on AMF community. Liu et al (2020) showed the influence of season and soil on AMF community in mountainous areas. The results of these studies show that soil and vegetation are the main environmental factors affecting AMF community, and that climate, seasonality and precipitation all indirectly affect AMF community through soil, but the types, magnitude and trends of the effects of soil factors on AMF community vary from different studies and need to be explored in depth.…”
Section: Introductionmentioning
confidence: 99%
“…The stage of plant development is an important driver in shaping rhizospheric communities, leading to a dynamic exchange between plant growth and the host's microbiota composition [4,70,71]. We found that the bacterial diversity and richness was the highest during the fruiting stage, although there was no significant difference found in the other three stages.…”
Section: Growth Stage Dynamics Of Micobiomes Diversity and Structure ...mentioning
confidence: 71%
“…In contrast, the fungal richness and diversity of Pinus tabuliformis roots decreased during warm seasons [72]. Likewise, Liu et al [71] observed the greatest arbuscular mycorrhizal richness and diversity in the spring for Clematis fruticosa. These observations not only further support the possibility that the season and/or plant development stage impacts the microbial community diversity and richness, but also that the specific effects could be varied due to the differences in species, and other biotic or abiotic factors.…”
Section: Growth Stage Dynamics Of Micobiomes Diversity and Structure ...mentioning
confidence: 95%